Effects of Calendula Officinalis and Hypericum Perforatum on Antioxidant, Anti-Inflammatory, and Histopathology Indices of Induced Periodontitis in Male Rats - Nader Tanideh; Vajiheh Ghafari; Reyhaneh Ebrahimi; Raha Habibagahi; Omid Koohi-Hosseinabadi; Aida Iraji (Shiraz University of Medical Sciences, 2020)
Statement of the Problem: Periodontitis is one of the most common bacterial infections of the oral cavity. It is important to find adjunctive methods for chemical treatment of periodontitis with less complications and proven therapeutic properties. Purpose: The aim of this study was to compare the effects of Calendula officinalis and Hypericum perforatum on antioxidant, anti-inflammatory and histopathologic indices of induced periodontitis in male rats. Materials and Method: In this experimental animal study, forty adult male Sprague-Dawley rats were randomly divided into 4 groups (n=10) and then experimental periodontitis was induced by 3-0 nylon non-absorbable ligature. Each group was treated for 10 days as follows: 1) H. perforatum hydroalcoholic extract, 1000 mg/kg/daily, orally; 2) C. officinalis hydroalcoholic extract, 1000 mg/kg/daily, orally; 3) a mix of the two plants, 1000 mg/kg/ daily, orally, 4) normal saline solution. At the end of study, blood sample were obtained via cardiocentesis, the rats were euthanized, and their maxillae were removed. The samples were analyzed for histopathological scores and total antioxidant capacity and IL-1β were measured. Results: Mixed hydroalchoholic extract of H. perforatum and C. officinalis decreased IL-1β (4.3020±0.63), and increased the antioxidant parameter in comparison to the control group (3.1192±0.43) (p< 0.001). There were significant histopathological differences between the treatment groups and the control group. Conclusion: Mixed hydroalchoholic extract of H. perforatum and C. officinalis might be considered as an adjunctive treatment for periodontitis.